Different Types of Physical Activity and Metabolic Control in People With Type 1 Diabetes Mellitus - Štotl, Iztok; Kambič, Tim; Hadžić, Vedran; Zdolšek, Anže (Frontiers in Physiology, 2019)
Background: The aim of presented cross-sectional study was to determine the association of different types of physical activity with metabolic control in people with type 1 diabetes. Materials and Methods: A total of 109 adult subjects with type 1 diabetes were asked to complete the non-exercise activity thermogenesis (NEAT) questionnaire, the hypoglycemia questionnaire and the World Health Organization Global Physical Activity Questionnaire (GPAQ) which was used to assess moderate (MPA) and vigorous physical activity (VPA). Results: NEAT score (p<0.001) and total duration of work as assessed with GPAQ (p=0.007) were positively associated with chronic glycemic control when controlled for sex, BMI and continuous glucose monitoring system use. We could not confirm such association with total leisure time physical activity assessed with GPAQ (p=0.443), though. Multivariate regression model controlled for sex showed positive effects of HbA1c (p=0.011), age (p=0.035) and negative effect of NEAT score (p=0.001) on BMI. Systolic blood pressure was positively associated with duration of MPA (p=0.009) and VPA (p=0.012), but not with NEAT score (p=0.830) when controlled for sex and BMI. NEAT score and VPA were positively associated with HDL levels when controlled for sex and BMI. Controlled for sex and BMI, higher values of VPA were significantly associated with lower levels of total cholesterol (p=0.009) and LDL (p=0.005). Conclusions: Higher levels of NEAT are associated with some favorable metabolic effects in adult people with type 1 diabetes, but may also present an additional burden for them with more challenging environment regarding glycemic control.